O processo de alfabetização no ciclo alfabetizador: reflexões sobre a realidade cotidiana em escolas públicas estaduais - Veronez, Marisângela Nandi (2020)
This research focuses on the effectiveness of the literacy cycle in the daily reality of public schools. It is based on the understanding that from the pedagogical point of view, this educational organization presents the possibility of disposition of school time and space, of respecting the rhythms and learning processes of children, of the elimination of the repetition culture established in the school and of preserving students self-esteem, that its effectiveness in the daily practice of schools requires objective conditions for its materialization, besides the existing legal determinants. So, the objective was to learn how the literacy cycle has been carried out in the daily practice of state public schools in the municipality Braço do Norte/SC. To achieve this objective, it was necessary to: verify the objective conditions for the materialization of the cycle at school; observe the conditions in which the literacy cycle is being carried out; and to identify the external and internal determinants of the school, necessary to make feasible the children's literacy from the perspective of the cycle. This research was guided by the perspective of historical-dialectical materialism, with the purpose of unveiling and knowing the unknown in the search for the transformation of reality. It is characterized by the movement of thought through the historical materiality of the life of men in society, in other words, it is about unraveling, through the movement of thought, the essential laws that determine the organizational form of men during human history, starting from the articulation between the singularity, the particularity and the universality, whose relations are fundamental to understand the reality, because the appearance, manifestation or phenomenon, is only one aspect of this reality. To research the literacy cycle in this perspective and seek is to understand it in this “movement” in front of external and internal determinants of the school. The data were obtained through documentary analysis and semi-structured interviews with literacy teachers and school managers who work directly with the literacy cycle in state schools in the municipality of the research field. The analysis carried out show that schools are aware of the laws and regulations about the cycle and even evidence of attempts to implantation. Schools are willing to organize pedagogical practice considering the cycle, but this is not the guiding guideline for the work developed in the institutions. The school reality and everyday circumstances make it difficult for the materialization of this policy. There is no availability of time and space for teachers to study, plan and discuss this form of work in practice in a collective and integrated way with guidance and pedagogical attendance. The only moments to share experiences and situations experienced in the classroom, are recess and Class Councils held every quarter, in order to make pedagogical practice feasible from the perspective of the cycle. Keywords: Literacy cycle. Literacy process. School context.